Orbital aspergillosis mimicking giant cell arteritis - Cheng, TC; Jemaima Che Hamzah,; Amin A,; Mae-Lynn Catherine Bastion, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
Orbital aspergillosis is a very rare, debilitating disease which can present solely with painful optic neuropathy and mimic giant cell arteritis in an elderly person. We report a case of orbital aspergillosis in a 65-year-old Malay man who presented with unilateral gradual blurring of vision and ipsilateral headache. Our initial working diagnosis was giant cell arteritis. Unfortunately, patient’s condition worsened with intravenous corticosteroid and developed into orbital apex syndrome. Imaging and biopsy results showed evidence of orbital aspergillosis. Patient lost his eyesight due to the wrong initial working diagnosis. This report is to emphasize that although giant cell arteritis is also a sight and life-threatening condition, it is rare among Asian populations. We need to take into account the epidemiology of the disease and look into any other differential diagnoses when the presentation is atypical.